Mutations in PilZ domains of newly discovered bacterial β-(1,3;1,4)-mixed linkage glucan synthases modulate polysaccharide production - Rebecka Karmakar Saldivar; Shu-Chieh Susie Chang; Sheileza Rajkumari; Rico A. Pratama; Yen-Ting Lin; Mu-Rong Kao; Christina Divne; Chi-Kung Ni; Yves S.Y. Hsieh (Carbohydrate Polymers, 2026)

Two glycosyl transferase 2 genes from the gram-positive bacterium Clostridium ventriculi encode (1,3;1,4)-β-D-glucan synthases - Shu-Chieh Chang; Rebecka Karmakar Saldivar; Mu-Rong Kao; Xiaohui Xing; Chun-Hong Yeh; Jiun-Jie Shie; D. Wade Abbott; Philip J. Harris; Yves S.Y. Hsieh (Carbohydrate Polymers, 2024)

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.